2x+3=7x+(-42)

Simple and best practice solution for 2x+3=7x+(-42) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=7x+(-42) equation:


Simplifying
2x + 3 = 7x + (-42)

Reorder the terms:
3 + 2x = 7x + (-42)
3 + 2x = 7x + -42

Reorder the terms:
3 + 2x = -42 + 7x

Solving
3 + 2x = -42 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
3 + 2x + -7x = -42 + 7x + -7x

Combine like terms: 2x + -7x = -5x
3 + -5x = -42 + 7x + -7x

Combine like terms: 7x + -7x = 0
3 + -5x = -42 + 0
3 + -5x = -42

Add '-3' to each side of the equation.
3 + -3 + -5x = -42 + -3

Combine like terms: 3 + -3 = 0
0 + -5x = -42 + -3
-5x = -42 + -3

Combine like terms: -42 + -3 = -45
-5x = -45

Divide each side by '-5'.
x = 9

Simplifying
x = 9

See similar equations:

| 5x^4-12x^2+3=0 | | 3k=5k+7 | | -11+3x=x-15 | | 4.905x^2-4x-22=0 | | 2x^2-1528x+2821=0 | | 5p+14=29 | | m/4=2 | | 8r^2-6r-9=0 | | 9x-4=5x+32 | | 2-4x=12+x | | 5x-7=-4x+-25 | | 6(x+2)=60-6x | | 3-10=2+32 | | -2x+3x=-6x+13x | | 12/23*2/4*(11/12-5/18) | | 4x-7=-9x+84 | | 24x+38=14x | | 5v+9=33 | | 42/7a | | (4x+1)(7x-6)=0 | | 5x^2-7+2=0 | | 9x+1=3x+31 | | (2x+4)*(x-1)-36=0 | | 180x^4-108x^3-107x^2+36x+20=0sol | | 4x=46-10 | | 3(2x+1)+5=7-3x | | 9x-7=-2x+-40 | | 4/5c•4c/18 | | 7x-8=9x+(2) | | Ln(2.5x)=3 | | 13x-66=90 | | 3x+5y-7x=37findx |

Equations solver categories